Texture analysis of deformation induced martensite in an AISI 301L stainless steel: microtexture and macrotexture aspects - Hamilton Ferreira Gomes de Abreu; Marcelo José Gomes da Silva; Luís Flávio Gaspar Herculano; Harry Bhadeshia (Materials Research, 2009)
Experiments have been conducted to study the strain induced transformation from austenite to martensite in a metastable AISI 301LN austenitic stainless steel, deformed by uniaxial tension applied along rolling direction. Samples deformed 10 and 20% have shown the presence of α´ martensite phase. Measured pole figures of martensite phase were compared to calculated ones, assuming no variant selection and selection of variants where interaction between stress and the plate of martensite adds to the driving force transformation variants. EBSD (electron back scatter diffraction) microtexture experiments and macrotexture X-ray diffraction were performed. The orientation distribution functions (ODFs) from measured pole figure data were calculated. The measured results were compared with calculated results in both polycrystalline and single crystal samples of austenite. The results showed that the calculated textures based in a process of variant selection consistent with Patel and Cohen's theory, which emphasizes a mechanical component of free energy, were in good agreement with measured texture.